Family Life- and Identity-Related Rights of the Child - Wedeł-Domaradzka, Agnieszka (Children’s Rights in Regional Human Rights Systems, 2024)
This study addresses the issue of family life in the context of private life – the issue of identity. The study aims to provide insights regarding the challenges associated with ensuring the right to family life and identity prevalent today. The analysis is conducted based on regional standards of the Council of Europe, mainly the European Convention for the Protection of Human Rights and Fundamental Freedoms and the European Court of Human Rights case law, which has developed from it. The scope of the analysis includes the right to family life and right to identity in the European Court of Human Rights, the origin of the child and its relation to the right to family life and identity, child registration and its relation to the right to family life and identity, the child’s name and surname as elements shaping the child’s identity, nationality, and identity, parent-child contact, and the right to maintain identity. The study highlights key trends and challenges related to respect for identity in the context of existing and new phenomena occurring in the societies of Central European countries.Keywords:  family life, child, best interests of the child, right to privacy, identity, European Court of Human Rights, European Convention of Human Rights, parental rights